Doping and supplementation applied in Bydgoszcz gyms - Mirosława Szark-Eckardt; Łukasz Kowalczyk; Hanna Żukowska; Wioletta Łubkowska (Nicolaus Copernicus University in Toruń, 2015)
The aim of the study is to determine what kind of doping and what kind of supplements are in use by those exercising in gyms in Bydgoszcz. The study was conducted among people practicing in gyms in Bydgoszcz. Method that was used was a diagnostic survey. Based on research it can be concluded that the anabolic androgenic steroids are the most commonly used doping. It can be also conclude that a significant proportion of respondents is using creatine to improve the appearance of the figure, which affects the quality of training. Almost all respondents claim that supplementation is a phenomenon commonly occured.